Algorithm animation for cryptanalysis of caesar and hill ciphers / Sapiee Haji Jamel and Giuseppina Sherry Sayan - Jamel, Shafie; Sayan, Giuseppina Sherry (Penerbit UiTM (UiTM Press), 2009)
Cryptographic algorithms are usually kept secret and the complexity of each algorithm is based on mathematical or statistical analysis. However, in modern cryptography, the strength of each cryptographic algorithm should only rely on the secret key(s) used to ensure that there is no trap door embedded in the algorithm. This new trend gives an advantage to cryptanalyst since types of algorithm(s) used are no longer a secret. Cryptanalysis steps can be easily explained using algorithm animation that can be easily integrated with any e-learning platform. This paper presents an algorithm animation for cryptanalysis of Caesar Cipher using ciphertext only attack and Hill Cipher using Brute force technique. Each of the steps involved in the cryptanalysis is shown using animation technique developed using Macromedia Flash. This application is suitable for e-learning activities for students interested in the cryptanalysis of block cipher.